The use of non-adapted anaerobic consortium in batch reactors enable to couple polychlorinated biphenyl degradation and community adaptation - de Lima e Silva, Mara Rúbia; Feitosa de Lima Gomes, Paulo Clairmont [UNESP]; Okada, Dagoberto Yukio; Sakamoto, Isabel Kimiko; Varesche, Maria Bernadete Amancio (Taylor & Francis, 2020)
The removal of polychlorinated biphenyls (PCBs) and PCB biosorption was investigated in anaerobic batch reactors with non-adapted sludge fed with 1.5 mg L−1 of six PCB congener (PCB 10, 28, 52, 153, 138 and 180), mineral medium and co-substrates. PCBs were analyzed by gas chromatography using headspace solid-phase microextraction (HS-SPME). In the methanogenic reactor the methane production, COD (Carbon Organic Demand) removal (90% of initial 2292.60 mg L−1) and consumption of volatile organic acids were verified. Nevertheless, anaerobic activity was not observed in the reactor with inactivated biomass and biosorption range of 38% to 89% was measured for distinct PCB congeners in this reactor. The PCB removal was calculated from the PCB bioavailable (not biosorbed) and reached 76% of total PCBs. The selection of some representatives of the Thermotogaceae family, Sedimentibacter and Pseudomonas at 101 days of operation in the methanogenic reactor was correlated with PCB degradation. In addition, the various removal rates for each PCB congener indicate that the removal depends on bioavailability. The selection of the former non-adapted microbiota in the methanogenic reactor combined with PCB degradation occurred at 101 days. These results allow to assert that it is possible to simultaneously couple PCB degradation and community selection, without the previous adaptation step, which is a time-consuming stage.
Keywords: bioavailability; PCB; Pseudomonas; Sedimentibacter; Thermotogaceae